The Implementation of Online Learning from Teachers’ Perspective - Silky, Dwi Rohmaniatu; Suryaman, Maman (Universitas Islam Negeri Raden Intan Lampung, 2022)
Formal education that used to be done face-to-face in schools is now being conducted online. Changes in the implementation of this learning certainly have an impact on various parties. The purpose of this study was to determine the perception of the implementation of online learning from the teacher's point of view and what obstacles were encountered. The research method used in this research was descriptive-qualitative method with questionnaires and interviews as instruments. As a result, there were three obstacles in the implementation of online learning, namely quotas and signals, dependence on parents, and boredom of students in the learning process. The media used by the teachers were WhatsApp, Zoom Meeting, Edmodo, Google Classroom, Google Meet, Google Form, and Youtube. All of them hope that face-to-face class activities as usual can be carried out soon because the effectiveness of learning is better if it is done face-to-face.